Diastereoselective and enantioselective conjugate addition reactions utilizing α,β-unsaturated amides and lactams - Byrd, Katherine M. (Beilstein Journal of Organic Chemistry, 2015)
The conjugate addition reaction has been a useful tool in the formation of carbon–carbon bonds. The utility of this reaction has been demonstrated in the synthesis of many natural products, materials, and pharmacological agents. In the last three decades, there has been a significant increase in the development of asymmetric variants of this reaction. Unfortunately, conjugate addition reactions using α,β-unsaturated amides and lactams remain underdeveloped due to their inherently low reactivity. This review highlights the work that has been done on both diastereoselective and enantioselective conjugate addition reactions utilizing α,β-unsaturated amides and lactams.
Keywords: α,β-unsaturated amides; α,β-unsaturated lactams; conjugate addition; Michael addition